Comparative Analysis of Treatment Outcomes in Endometrial Cancer: Hormonal Therapy vs. Chemotherapy in Postmenopausal Women - Zeb, Marriam; Ahmed Memon , Hina Nisar; Nadeem, Habibah; Altaf, Rabia; Bano, Khalida; Ghafoor, Najaf Abbas (Indus Journal of Bioscience Research, 2025)
Hormonal and chemotherapy therapies were studied in postmenopausal women using a quantitative study. Because hormones play a role in endometrial cancer, this research worked to close a major gap in patient management. Total of 250 patients were randomly selected from oncology centers within the given geographic area. After patients had finished their treatment, the team surveyed them to find any improvements to their health and any changes from using the drugs. To analyze carefully what affects quality of life, regression analysis was applied, Chi-Square analysis examined relationships between the treatments and side effects and an independent sample t-test was used to compare average quality of life scores between the groups. Upon completing the regression analysis, the results showed that treatment type, patient age, how advanced the tumor was and the number of health problems determined a person’s quality of life, with chemotherapy being much less favorable than hormonal therapy. The analysis found that side effects from chemotherapy were more common than those from radiation. Patients in the hormonal therapy group reported a better quality of life than patients treated with chemotherapy. In agreement with earlier studies, they advise that researchers developing postmenopausal treatments should weigh how much women may gain from the medication against the possible side effects. Based on the study, doctors should use a strategy that combines information about the disease, the patient’s health problems and their well-being. The results of future qualitative and long-term studies can clarify patient preferences, their long-term outcomes and the impact of various therapies. The research finds it important to give women who are postmenopausal supportive, effective and tailored treatment for endometrial cancer